Emotional and social competencies and perceptions of the interpersonal environment of an organization as related to the engagement of IT professionals - Pittenger, Linda M. (Frontiers in Psychology, 2015)
Diminishing levels of worker productivity and increased employee turnover have become a costly proposition for today’s organizations. Much of the blame for this is a decrease in employee engagement and actual complete disengagement of workers, resulting in tremendous impacts to the achievement of organization goals. In particular, research has focused on IT professionals, which have been found to be the least engaged group of workers in organizations. With such conclusions repeatedly discovered, it is surprising that IT employee engagement has been largely ignored as a focus of scholarly research. This study examines the relationship between specific behavioral competencies and characteristics of the organization environment and the relationship between the organizational environment characteristics and components of employee engagement. We used validated instruments to perform a quantitative study and collected data from 795 IT professionals in North America to test the effects of behavioral competencies and role breadth self-efficacy (RBSE) on the organization environment and in turn, the organization environment on employee engagement. The findings revealed two behavioral competencies − achievement orientation and influencing others − powerfully impact the three sub-constructs of the organization environment: vision, compassion and overall positive mood, which in turn, influence the engagement (dedication, vigor, and absorption) of IT professionals at work. We contribute to literature by revealing specific behavioral and organizational factors found to positively impact engagement. Our findings contribute to practitioners by enabling them to more effectively select, develop and promote IT professionals. By better understanding what factors differentiate the performance of IT professionals, practitioners can implement tools and programs to increase employee satisfaction, engagement, and retention, resulting in higher productivity, quality, and profitability.